Social Policy Programme “The Family 500+” – Assumptions, Results, and Costs of Functioning: Is It Worth? - Anna Owczarczyk (Polish Political Science Yearbook, 2021)
The unfavorable demographic situation and the falling number of births resulted in an increased interest among Polish politicians in introducing tools to social policy that would reverse this negative trend. Implemented to social policy by Prawo i Sprawiedliwość Party in 2016, the “Family 500+” benefit has become such a tool. According to the government’s intention, this financial aid for families with children aims to reverse the decline in the number of births observed for many years and reduce the scale of poverty among families with the most complex financial situation. After several years of the “Family 500+” Program in force, it is difficult to clearly define whether the goals were achieved and whether the expenses for financing the program were adequate to the results. The aim of the article is an attempt at the assessment of the functioning of the Family 500+ Programme. Both the statutory assumptions of the programme, the costs of its functioning, and its results so far were analyzed. The central part of the analysis covered the period 2016–2019.